Exploring Teachers' Perceptions of TPACK Integration: A Study on Education Levels, Certification, and Kelompok Guru Penggerak - Sukri, Febry Afrilianty; Lukman A.R Laliyo; Sri Endang Saleh (Cita konsultindo, 2025)
This study explores teachers' perceptions of the integration of TPACK (Technological Pedagogical Content Knowledge) in learning practices, particularly in Gorontalo, by considering aspects of education level, Teacher Activist group, and teacher certification. Using a quantitative approach with Kruskal-Wallis test, this study involved 303 respondents from various education levels. The analysis showed that there were no significant differences in teachers' perceptions based on education level and certification status, but there were significant differences in the Master Teacher group. The study revealed barriers to TPACK integration such as limited access to technology and training, and resistance to change, especially in areas with minimal technological infrastructure. The implications of this study emphasize the importance of teacher capacity building through continuous training and equal access to technology to improve learning outcomes in the 21st century.